2000
DOI: 10.1001/jama.283.22.2955
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Sunscreen Use and the Development of New Nevi in White Children

Abstract: Our data indicate that broad-spectrum sunscreens may attenuate the number of nevi in white children, especially if they have freckles. JAMA. 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
184
2
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(199 citation statements)
references
References 33 publications
6
184
2
7
Order By: Relevance
“…The UVA hypothesis accounts for the significantly higher prevalence of melanocytic nevi that was found in children whose parents regularly applied UVB sunscreens to them (43), although another study found a minimal reduction (44). It is consistent that the number of sunburns the child had experienced was not associated with nevus count (43).…”
Section: Discussionmentioning
confidence: 96%
“…The UVA hypothesis accounts for the significantly higher prevalence of melanocytic nevi that was found in children whose parents regularly applied UVB sunscreens to them (43), although another study found a minimal reduction (44). It is consistent that the number of sunburns the child had experienced was not associated with nevus count (43).…”
Section: Discussionmentioning
confidence: 96%
“…This same concern has been advanced in studies showing that population that used sunscreen had greater melanocytic nevi, an indicator of sun exposure [9,10,11,12,18,19,148], although a recent study from Canada found that sunscreen reduced nevi in a randomized prospective design [74]. The negative effects of sunscreen may be most evident when individuals choose to be outdoors in the sun rather than when their time in the sun is determined by factors out of their control such as work schedules.…”
Section: Does Sun Safety Increase Time In the Sun?mentioning
confidence: 93%
“…There is an extensive literature that accords to sunscreens the capacity to reduce DNA damage (Gallagher 2005;Lee et al 2005;Mahroos et al 2002;Young et al 2000;Gallagher et al 2000a;Gallagher et al 2000b). Gallagher of the Cancer Control Research Program of the British Columbia Cancer Agency (2005) reported that ''a number of trials have provided good evidence that, when applied consistently, sunscreens can realistically play a role in reducing the risk of squamous cell carcinoma'' (244).…”
Section: Examination and Vettingmentioning
confidence: 99%